I01 Msh3-targeting antisense oligonucleotides halt CAG repeat expansions in Huntington's disease IPSC-derived neurons. (12th September 2022) - Bunting, Emma; Donaldson, Jasmine; Olive, Jessica; Kordasiewicz, Holly; Bennett, Frank; Cumming, Sarah A; Monckton, Darren G; Flower, Michael; Tabrizi, Sarah J
Abstract : Huntington's disease (HD) is a fatal neurodegenerative condition caused by an expanded CAG repeat in the huntingtin gene (HTT). This repeat tract continues to expand throughout life in a process called 'somatic expansion', driving disease onset. MSH3, a DNA mismatch repair gene, has been shown to drive somatic expansion in multiple HD model systems. Unlike some of the other DNA repair genes implicated in this process, MSH3 is known to tolerate loss-of-function variation in humans, making it an ideal therapeutic target. This study investigates the therapeutic potential of MSH3 lowering, by treating iPSC-derived medium spiny neurons from HD patients with an MSH3 ASO and measuring its effect on somatic expansion over time. We show that the MSH3 ASO is taken up successfully by HD iPSC-derived neurons, with dose-dependent knockdown of MSH3 and no effect on cell viability. Using fragment length analysis to size the CAG repeat, we demonstrate that MSH3 ASO treatment of these cultures slows somatic expansion in a dose-dependent manner. Strikingly, the maximal dose ( 80% knockdown) completely halts somatic expansion, with a trend towards small contractions of the repeat (p = 0.068). We are investigating contraction dynamics using small-pool PCR and PacBio single molecule sequencing. At the same dose, the MSH3 ASO still reduces somatic expansion in neurons derived from an isogenic FAN1 KO line by 3-fold. In this manner, our study demonstrates the therapeutic potential of MSH3 ASOs, which could delay, or even prevent, the onset of symptoms in Huntington's patients by preventing further somatic expansion of the HTT CAG repeat. Support: CHDI, MRC.